Estrategias metodológicas innovadoras en el proceso de enseñanza en Estudios Sociales - Villacis Coque, Lucia Liliana (2023)
The purpose of this research work is to apply innovative methodological strategies in the teaching process of Social Studies, in the students of Unfinished Schooling of the eighth, ninth and tenth years of Basic General Education of the all ABC program, of the Educational Unit "Salcedo ”, San Miguel Parish, Salcedo Canton, Cotopaxi Province”, the research was based on a qualitative approach, since it allows understanding the reality of the educational context from its own environment, the modalities on which it is based are documentary, bibliographic and field , was based on a group of 35 unfinished school students from phases eight, nine and ten that constitute a parallel, theoretical inductive empirical observation methods were used; the research techniques and instruments: interview-interview guide, observation-observation guide, which made possible the diagnosis of the study context, associated with the application of innovative methodological strategies in the area of social studies, the research design is based on In the action research, the specific methods of the specialty to be used in the investigation were the own method, the analysis was carried out through an information processing matrix, which was obtained from the investigated subjects. This process is based on the analysis of content to agree with the variables established in the research, the Atlas ti program was also used, which allows analyzing questions, coding, making maps and networks and interpreting the results of qualitative research, it concluded that by applying innovative methodological strategies, students feel motivated to learn more about the Social Studies subject